2010
DOI: 10.1089/jir.2009.0025
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Interferon Response Through Toll-Like Receptor 3 Impacts Viral Pathogenesis and Pulmonary Toll-Like Receptor Expression During Respiratory Syncytial Virus and Influenza Infections in the Cotton Rat Sigmodon hispidus Model

Abstract: Interferon (IFN) therapy in humans often causes flu-like symptoms by an unknown mechanism. Poly ICLC is a synthetic dsRNA and a toll-like receptor 3 (TLR3) agonist with a strong IFN-inducing ability. In this work we analyzed the effect of poly ICLC on pulmonary responses to influenza and Respiratory Syncytial Virus (RSV) infections in the cotton rat (S. hispidus) model. Viral replication, pulmonary inflammation, and expression of IFN, TLR, and chemokines were monitored and compared. Antiviral effect of poly IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…Histopathological lesions associated with hRSV challenge in cotton rats consist of mild to moderate bronchiolitis or pneumonia, sloughed epithelial cells, and patchy atelectasis (18,93,94). The cellular and biochemical responses to virus challenge are relatively limited, primarily lymphocytes associated with moderate increases in expression of MIP-1␣/CCL3, MCP-1, and IFN-␥ (18,19,94) and no clear evidence of significant clinical signs of URTD of LRTD (18,93). No specific age dependency in the susceptibility to hRSV has been reported although elderly cotton rats exhibit delayed viral clearance (20).…”
Section: Heterologous (Nonhuman) Hrsv Modelsmentioning
confidence: 99%
“…Histopathological lesions associated with hRSV challenge in cotton rats consist of mild to moderate bronchiolitis or pneumonia, sloughed epithelial cells, and patchy atelectasis (18,93,94). The cellular and biochemical responses to virus challenge are relatively limited, primarily lymphocytes associated with moderate increases in expression of MIP-1␣/CCL3, MCP-1, and IFN-␥ (18,19,94) and no clear evidence of significant clinical signs of URTD of LRTD (18,93). No specific age dependency in the susceptibility to hRSV has been reported although elderly cotton rats exhibit delayed viral clearance (20).…”
Section: Heterologous (Nonhuman) Hrsv Modelsmentioning
confidence: 99%
“…IP-10 is a chemokine that is known to attract T cells and NK cells. In cotton rat treated with a TLR3 agonist then infected with HRSV, it was shown that type I IFN responses can augment lung inflammation in this model (Boukhvalova et al, 2010). …”
Section: Hrsv Infection Of Cotton Ratsmentioning
confidence: 98%
“…Studies in mice suggest that poly-ICLC and liposome-encapsulated poly-ICLC are safe and provide broad-spectrum protection against seasonal and highly pathogenic avian influenza A viruses, as well as RSV and SARS virus [89]. However, in a cotton rat model of RSV and influenza infection, intranasal administration of antiviral doses of poly-ICLC induced lung inflammation [90]. Comparative transcriptional analysis upon subcutaneous administration of poly-ICLC indicated that it induces innate immune responses of similar magnitude to a live viral vaccine in humans [91].…”
Section: Tlr3mentioning
confidence: 99%
“…RSV-infected BALB/c mice treated with poly-ICLC showed significantly reduced inflammation and clinical scores for the disease [171]. However, in contrast to the murine model, poly-ICLC treatment resulted in increased pathology during RSV infection in cotton rats [90]. In addition, due to important differences in the TLR signaling pathways in animal models and humans, many drugs tested with encouraging results in animal models failed to show much effect in human studies.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%